La traducció catalana de la «Història de les Amors de París e Viana» - Ferrando, Antoni (Caplletra. Revista Internacional de Filologia, 2007)
The text of the three Catalan editions of «Història de les amors de París i Viana», published in Barcelona and Girona in the last decade of the fifteenth century, shows a linguistic orientation towards Castilian and Italian onomastics. It has led to postulate two hypotheses on its textual dependence: a Castilian origin and an Italian origin. A revision of the text as translation and adaptation for the printing allows to ascertain the confluence of two linguistic layers: one, of the first half of the fifteenth century, which explains the persistence of archaic features and the Italian onomastics, and another, contemporary with the edition, which accounts for the Castilian orientation of the textas a modernising option within the sociolinguistic context of the reign of Ferdinand the Catholic (1479- 1516).